2022
DOI: 10.56093/ijas.v91i3.112535
|View full text |Cite
|
Sign up to set email alerts
|

Economic appraisal of Kinnow production in Sirsa district of Haryana

Abstract: An economic analysis of kinnow has been presented through studying their costs and returns. The present study was carried out during 2017-18 in Sirsa district of Haryana. A sample of 30 kinnow respondents was taken purposively from various villages in Mandi Dabwali block of Sirsa district of Haryana. The results of the study revealed that average first year establishment costs per hectare for kinnow has been worked out to be ₹127979. Whereas, per hectare per year returns from kinnow orchard have been worked ou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 4 publications
0
0
0
Order By: Relevance
“…The maximum value for total sugars might be due to conversion of polysaccharides into soluble sugars, dehydration and transformation of certain cell wall materials like hemicelluloses and pectins and also due to decrease in ascorbic acid content. The results are in line with the findings of Santos et al [24], Kumar et al [25] and Navarro et al [26], the research was carried out on citrus fruits and authors found out that LDPE packaging was generally more effective in preserving the total sugars content compared to PP and PET packaging.…”
Section: Phsupporting
confidence: 91%
“…The maximum value for total sugars might be due to conversion of polysaccharides into soluble sugars, dehydration and transformation of certain cell wall materials like hemicelluloses and pectins and also due to decrease in ascorbic acid content. The results are in line with the findings of Santos et al [24], Kumar et al [25] and Navarro et al [26], the research was carried out on citrus fruits and authors found out that LDPE packaging was generally more effective in preserving the total sugars content compared to PP and PET packaging.…”
Section: Phsupporting
confidence: 91%